Freedom of Speech in the Face of Terrorism – Selected International Law Regulations - Kowalska, Samanta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The essay presents freedom of speech from the perspective of international law regula-tions. The phenomenon of terrorism is one of the most asymmetrical, amorphous and hybrid threats to international security and human rights. The author discusses freedom of speech in the context of anti-terrorism measures. Freedom of speech is a legal and axiological framework of democratic society. The media constitute an important source of information about social pathologies and threats. Terrorists use the media to depreci-ate the law and the state, and to generate chronic fear in society. The essay stresses the fact that a rational and informed approach to human rights should serve as a reference point for anti-terrorism. However, one cannot limit individual freedom in an arbitrary way. Public discourse helps reach an objective perception. This prevents the creation of a multiplied image, pseudo-reality and “double standards” for freedom of speech.